UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG MELALUI MEDIA SIMETRI PUTAR KELAS III SDN BANJARSUGIHAN I/116 SURABAYA - Widya Riska Nur Anisa; Vicky Dwi Wicaksono; Titik Indrayani; Sri Wachyuni; Kasmiatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve mathematics learning outcomes by using rotational symmetry media for class III SDN Banjarsugihan I/116 Surabaya by involving 20 students as participants in carrying out two action cycles consisting of planning, implementation, observation, evaluation and reflection stages carried out in each cycle. . The data analysis techniques used in this research are quantitative descriptive and qualitative descriptive. This research shows that student learning outcomes have increased. This is proven by the increase in the percentage of student learning outcomes in cycle I and cycle II, namely 13.5%. From 17 students who completed (75.5%) to 20 students who completed (89%). The average learning outcomes of students in Cycle I to Cycle II increased, namely from 75.5% to 89%.